The Narcissistic Skeptic and the Human Community: Shakespeare’s Coriolanus as Read by Stanley Cavell - MICHAŁ FILIPCZUK (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
In this paper, I reconstruct Cavellian reading of Shakespeare’s Coriolanus. Stanley Cavell stands out as an original interpreter of Coriolanus due to his perspective on its specific themes and motifs. While they have been explored in earlier – mostly psychoanalytical and political – interpretations of the play, Cavell studies them through the lens of his concept of narcissistic skepticism. Framing the question of the narcissistic skeptic versus the human community highlights the particular value of Cavell’s perspective. It incorporates a political theme within the context of a psychoanalytical approach, while simultaneously going beyond it and leading to a unique synthesis of both areas. As a result, it allows for conclusions to be drawn about the political nature of the human community and its defining characteristic, which Cavell identifies as being rooted in language.